2009
DOI: 10.1007/s00421-009-1082-x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and redox status after maximal aerobic exercise at high altitude in acclimatized lowlanders and native highlanders

Abstract: Exercise-induced increase in oxygen consumption leads to oxidative stress. On the contrary, hypoxia triggers oxidative stress despite decreased oxygen flux. Therefore, exercise under hypoxia may aggravate oxidative damage. Highlanders are expected to have better antioxidant capacity than lowlanders as a result of adaptation to hypoxia. The present study was undertaken to investigate the effect of exercise on antioxidant system in lowlanders and highlanders at high altitudes (HA). This study was conducted on ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…In agreement with previous studies (Blatteis and Lutherer 1976;Robinson and Haymes 1990), the greater fall in VO 2max after hypoxia and cold exposure may be explained by the fall in maximum heart rate and tighter binding of oxygen to hemoglobin due to a drop in core body temperature which will ultimately impair oxygen supply to the active muscle (Bergh and Ekblom 1979;Bhaumik et al 2008). Our previous study had shown that reduction in VO 2max and duration of maximal exercise facilitates lowlanders to maintain better antioxidant status at HA as compared to native highlanders with higher VO 2max and greater performance duration (Sinha et al 2009). In the present study, the effect of unequal VO 2max levels between SOJ 1 and SOJ 2 on antioxidant system at HA can be nullified because both groups had followed submaximal exercise as a part of their daily routine fitness schedule.…”
Section: Discussionmentioning
confidence: 96%
“…In agreement with previous studies (Blatteis and Lutherer 1976;Robinson and Haymes 1990), the greater fall in VO 2max after hypoxia and cold exposure may be explained by the fall in maximum heart rate and tighter binding of oxygen to hemoglobin due to a drop in core body temperature which will ultimately impair oxygen supply to the active muscle (Bergh and Ekblom 1979;Bhaumik et al 2008). Our previous study had shown that reduction in VO 2max and duration of maximal exercise facilitates lowlanders to maintain better antioxidant status at HA as compared to native highlanders with higher VO 2max and greater performance duration (Sinha et al 2009). In the present study, the effect of unequal VO 2max levels between SOJ 1 and SOJ 2 on antioxidant system at HA can be nullified because both groups had followed submaximal exercise as a part of their daily routine fitness schedule.…”
Section: Discussionmentioning
confidence: 96%
“…This might be caused by a single amino acid substitution in subunit 3 of the protein that alters inter-subunit interactions (Scott et al, 2010). The importance of reducing ROS production in preventing oxidative damage is emphasized by studies comparing high-and low-altitude human populations: oxidative damage at high altitudes is generally less in highlanders even though most (but not all) antioxidant enzyme levels are reduced (Gelfi et al, 2004;Sinha et al, 2009a;Sinha et al, 2009b;Sinha et al, 2010). It is presently unclear how these evolutionary changes relate to the ancestral acclimatization response, but they should nonetheless be important for improving cell function at high altitudes.…”
Section: Tissue O 2 Utilizationmentioning
confidence: 99%
“…Many of the studies assessing oxidative stress and exercise under hypoxic conditions have examined the effects of high altitude (i.e., 3000m) in field-based studies, with prior exposure of the participants commonly not reported (Joanny et al, 2001;Miller et al, 2013;Sanchari et al, 2010;Sinha et al, 2009). At rest, the ascent (Møller et al, 2001;Siervo et al, 2014;Taylor et al, 2012) and descent (González et al, 2005) from altitude has been shown to cause marked increases in lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…At rest, the ascent (Møller et al, 2001;Siervo et al, 2014;Taylor et al, 2012) and descent (González et al, 2005) from altitude has been shown to cause marked increases in lipid peroxidation. The participants in the current study had not been exposed to altitude for at least 4 months, minimizing the impact of prior exposure perturbing basal or exercise-induced redox state, which has previously been demonstrated in active individuals (Sanchari et al, 2010;Sinha et al, 2009). Our findings show that only selective biomarkers of oxidative stress were exaggerated following exercise under hypoxic conditions relative to normoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation